Síntese e caracterização de novos líquidos iônicos alcanosulfonatos de interesse ambiental - Back, Giselle (2019)
Twentieth century was characterized by rapid economic growth, which caused a large increase in environmental pollution. In response to the negative environmental impacts caused by human activities, especially industrial activities, some events came as a way to raise people awareness about the consequences of their actions, and several actions began to be taken to reduce environmental damage. The with environmental pollution served as a stimulus for the advent of the so-called green chemistry, which seeks sustainability through the synthesis and use of less environmentally harmful chemicals. An example of the application of these products is the replacement of common organic solvents and catalysts by the use of Ionic Liquids. Ionic liquids (IL’s) are liquid electrolyte substances at temperatures below 100 °C and are composed exclusively of ions. Synthesis of IL’s is generally divided into two stages, the first is the formation of zwitterion and the second is anionic exchange, the ionic liquid can be shaped according to the needs of the reaction. In this work four different zwitterions (4,5a-b) were synthesized from tributylamine and triisooctylamine, with 1,3-propanosultone and 2,4-butanosultone. From these, nine different alkaline sulfonate ionic liquids derived from alkylamines (6,7,8,9a-b) of environmental interest were synthesized,and from anionic exchange of IL’s8a-b,9b with sodium tetrafluoroborate (NaBF4), IL’s10a-b,11b were synthesized. To characterize the compounds, thermogravimetry (TGA), differential scanning calorimetry (DSC), infrared spectroscopy (IR) and nuclear magnetic resonance (NMR) analyses were performed. Through the analyses it was possible to observe the formation of the desired product, so that the compounds presented good yields.